Androgen Activity Is Associated With PD-L1 Downregulation in Thyroid Cancer - O’Connell, Timmy J.; Dadafarin, Sina; Jones, Melanie; Rodríguez, Tomás; Gupta, Anvita; Shin, Edward; Moscatello, Augustine; Iacob, Codrin; Islam, Humayun; Tiwari, Raj K.; Geliebter, Jan (Frontiers in Cell and Developmental Biology, 2021)
Thyroid cancer is the most prevalent endocrine malignancy in the US with greater than 53,000 new cases in 2020. There is a significant gender disparity in disease incidence as well, with women developing thyroid cancer three times more often than men; however, the underlying cause of this disparity is poorly understood. Using RNA-sequencing, we profiled the immune landscape of papillary thyroid cancer (PTC) and identified a significant inverse correlation between androgen receptor (AR) levels and the immune checkpoint molecule PD-L1. The expression of PD-L1 was then measured in an androgen responsive-thyroid cancer cell line. Dihydrotestosterone (DHT) treatment resulted in significant reduction in surface PD-L1 expression in a time and dose-dependent manner. To determine if androgen-mediated PD-L1 downregulation was AR-dependent, we treated cells with flutamide, a selective AR antagonist, prior to DHT treatment to pharmacologically inhibit AR-induced signaling. This resulted in a >90% restoration of cell surface PD-L1 expression, suggesting a potential role for AR activity in PD-L1 regulation. Investigation into the AR binding sites showed AR activation impacts NF-kB signaling by increasing IkBα and by possibly preventing NF-kB translocation into the nucleus, reducing PD-L1 promoter activation. This study provides evidence of sex-hormone mediated regulation of immune checkpoint molecules in vitro with potential ramification for immunotherapies.